PERAN OUTDOOR EDUCATION DALAM PEMBENTUKAN KECERDASAN EMOSIONAL SISWA SMP NEGERI 24 PENAJAM PASER UTARA - Fitriana, Vivi Fitriana; Indar Sabri; Anik Juwariyah; Martadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine in depth the role of outdoor education in the formation of emotional intelligence among students of SMP Negeri 24 Penajam Paser Utara. The background of this research is the gap between national educational aspirations which envision emotionally mature students and the factual reality of students' underdeveloped emotional regulation, empathy, and social skills. A qualitative approach with a single case study design was employed. Data were collected through participatory observation, in-depth interviews with students, teachers, and the principal, and documentation, then analyzed using Miles and Huberman's interactive model. Findings show that outdoor education at SMP Negeri 24 Penajam Paser Utara is implemented in a structured manner through three phases: opening, core experiential activities in the school environment, and reflection. Outdoor education contributes to developing all five components of students' emotional intelligence, self-awareness, self-regulation, motivation, empathy, and social skills, through authentic emotional experiences, group collaboration, and interaction with nature. Supporting factors include a conducive school environment and the teacher's active facilitation role, while inhibiting factors include limited time, unpredictable weather, and the greater challenge of managing students outside the classroom. This research has practical implications for developing experience-based learning programs in schools within the IKN buffer zone.